PERSPEKTIF ISLAM TERHADAP HOAKS DAN PENYEBARANNYA DI MEDIA SOSIAL - Mhd Tafsir Tambunan Mhd Tafsir Tambunan (Lembaga Sepercenter, 2024)
Hoaxes or fake news is a phenomenon that is increasingly prevalent in the digital era, especially on social media. In Islam, honesty and integrity of information are principles that must be upheld. This study aims to examine the Islamic view of hoaxes and its implications for Muslim society, especially in the context of social media. The research method used is a literature study with normative and sociological approaches. The results show that Islam strictly prohibits the spread of Hoaxes because it can cause slander, hostility, and social damage. Qur'anic verses such as QS. Al-Hujurat: 6, An-Nur 14-15 as well as the Prophet Muhammad's traditions are the main basis in prohibiting the spread of unverified information. In addition, this study also identifies factors that encourage the spread of Hoaxes on social media and provides recommendations for preventive measures based on Islamic values to overcome them.